Hydroponic Training for Women Farmers Group (KWT) in Jaten, Sendang Rejo, Yogyakarta - Hanifah Rahmi Fajrin; Puspita Dewi Wulaningrum; Muhammad Ilham Haidar (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
To optimize land and yards as well as to produce healthy plants and minimal pest disturbances can be done with hydroponic farming techniques. Hydroponic plants such as vegetables have high nutrition and are healthy because they are free from the use of pesticides. In addition, hydroponics can also beautify the yard or yard of the house. For this reason, in this community service, counseling will be carried out on how to grow crops using hydroponics. With this activity, it is hoped that Women Farmers Group (KWT) at Jaten, Sendang Rejo will be more productive and can make the best use of the land by farming. It can also save expenses on kitchen ingredients, such as vegetables, spices, etc. The hydroponic stages are carried out in several stages, namely: sowing seeds (water spinach and mustard), carrying out hydroponic workshops, and implementing hydroponic practices. Hydroponic activities have been carried out well, so that further plant care is necessary until the plants can be harvested.